Проблемы формирования и функционирования рынка труда в Украине - Семко, Л. (Социология: теория, методы, маркетинг, 2001)
The article presents the theoretical and methodological problems related to the labour market formation and functioning in Ukraine. Special attention has been given to the regional specific features of the market. There have been separately discussed the economic, organizational and social-psychological aspects of the employment policy.